Wayang Wong Sebagai Pusaka Keraton Yogyakarta - Supriyanto Supriyanto (Institut Seni Indonesia Surakarta, 2013)
Soedarsono has written widely on the subject of Yogyakarta style wayang wong (a traditional Javanese stage show) as a dramaturgical state ritual in the Yogyakarta Palace. In general, wayang wong is a dramaturgy that can be described as a wayang performance presented by human actors. The term wayang wong may refer to all dramaturgies but its stories are usually taken from the Mahabharata and Ramayana epics. Wayang wong includes dialogue which is performed by the dancers and is based on the art of wayang kulit or shadow puppet theatre. Based on the evidence found in a number of sources, it can be said that the creator of wayang wong in the Yogyakarta Palace was Sri Sultan Hamengku Buwono I who reigned from 1755 – 1794. From the time of Hamengku Buwono V, wayang wong was nurtured and developed until it reached its peak of existence during the reign of Sultan Hamengku Buwono VIII (1921 – 1939). During this period, wayang wong enjoyed its golden era, as could be seen from the number of wayang wong performances that were held, sometimes lasting for several days. However, after the death of Sultan Hamengku Buwono VIII, Yogyakarta style wayang wong experienced a decline in popularity. There were a number of different factors which led to the decline of this noble art form, including social and cultural factors, aesthetical factors, and the factor of patronage. Since its first appearance, traditional wayang wong was an important part of life, government, and state rituals in the Yogyakarta Palace. All of the Sultans from the Hamengku Buwono dynasty continued the tradition of wayang wong performances throughout their reign. In this sense, wayang wong as one of the noble cultures of the Yogyakarta court can also be understood to be a cultural heirloom. This has also been explained by Soedarsono in reference to the collection of serat kandha, or wayang wong story scripts that are kept in the Yogyakarta Palace. In addition, the position of wayang wong as a ritual performance was a blessing for the kawula dalem, or palace servants, who watched the performances. Performances of wayang wong in the Yogyakarta Palace were a form of state ritual which functioned as a ceremony to promote fertility and prosperity. The prayers surrounding this ritual were offered at the beginning and end of a performance and read by the pemaos kandha (narrator) of the wayang wong performance.Keywords : wayang wong, heirloom, court.